Gall stone dissolution with methyl tert-butyl ether: how to avoid complications. - Hellstern, A (1990)
Fifty of 52 patients with cholesterol gall bladder stones were treated with methyl tert-butyl ether. In 48 of 50 (96%) patients the stones dissolved after an average interval of 9.5 hours. Mean stone size was 1.7 cm (0.5-3.3 cm), mean stone number was 14.6 (1-70). Twelve patients (24%) complained of nausea, a burning sensation, or vomiting. In one patient bile leakage occurred and another suffered haematobilia (4%). The puncture set was improved, and a special basket was developed to extract stones that had escaped into the cystic duct. To prevent bile leakage or haemorrhage from the incision channel, a tissue adhesive was injected into the channel or ceruletid was administered subcutaneously before removing the catheter to induce contraction of the gall bladder. Thus we were able to treat 44 patients without any complications. Nausea and vomiting could be reduced if the treatment time was kept short and the perfusion volume was as low as possible. Methyl tert-butyl ether treatment is a successful treatment of gall bladder stones with few complications.